THE EFFECTIVENESS OF JOESIN TRANSLATION YOUTUBE VIDEO TO IMPROVE STUDENTS VOCABULARY MASTERY FOR X GRADE AT SMAN 1 SUKOMORO - Gustiara Ganefa; Triana Wuri Cahyanti (Universitas PGRI Mpu Sindok, 2025)
YouTube helps people learn. Joesin Translation’s YouTube video is a great resource for English language learners. This study looks at whether Joesin Translation’s YouTube videos help students learn vocabulary. It will compare the students’ vocabulary before and after watching Joesin Translation videos. It will also look at how much the students’ vocabulary improved. The study used a pre-test and post-test with a convenience sample. The whole class of X was included, with 35 students from class X-1. Tests were used to collect data, which was then analyzed. The study showed that students improved their vocabulary after watching Joesin Translation videos. The average pre-test score was 54.9, while the average post-test score was 84.9. There’s a big difference. The t-test showed a t-count of 8.9, higher than the t-table value. The N-Gain results showed a 69% score, showing a big improvement in vocabulary. This means that there were significant differences in vocabulary mastery for tenth graders at SMAN 1 Sukomoro in the 2023/2024 school year.